Enchanted Hacienda - Cervantes, J. C Jennifer C. (Toronto, Ontario, Canada Park Row Books, 2023)
Harlow Estrada returns to the enchanted Hacienda Estrada, a family farm in Mexico where her mother, sisters, aunt and cousins harness the magic of charmed flowers, but when she's chosen to watch over the farm, she panics since she, herself, is magic-less, until she opens her heart to love and creativity.
When Harlow Estrada is abruptly fired from her dream job and her boyfriend proves to be a jerk, her world turns upside down. She flees New York City to the one place she can always call home--the enchanted Hacienda Estrada. The Estrada family farm in Mexico houses an abundance of charmed flowers cultivated by Harlow's mother, sisters, aunt, and cousins. By harnessing the magic in these flowers, they can heal hearts, erase memories, interpret dreams--but not Harlow. So when her mother and aunt give her a special task involving the family's magic, she panics. How can she rise to the occasion when she is magicless? But maybe it's not magic she's missing, but belief in herself. When she finally embraces her unique gifts and opens her heart to a handsome stranger, she discovers she's far more powerful than she imagined.
111601
Keywords: Families -- Mexico -- Fiction; Family farms -- Mexico -- Fiction; Magic -- Fiction; Self-actualization (Psychology) -- Fiction; Flowers -- Fiction; Magic realist fiction; Romance fiction